Development and validation of a health and nutrition module for the project-level Women's Empowerment in Agriculture Index (pro-WEAI+HN) - Heckert, Jessica; Martinez, Elena M.; Seymour, Greg; Pereira, Audrey; Roy, Shalini; Kim, Sunny S.; Malapit, Hazel J. (Wiley, 2023)
Agricultural development projects increasingly aim to improve health and nutrition outcomes, often by engaging women. Although evidence shows such projects can improve women's and children's health and nutrition and empower women, little is known about their impacts on women's health- and nutrition-related agency and the extent to which impacts emerge through women's empowerment, largely due to a lack of instruments that measure the dimensions of women's agency that are directly relevant to health and nutrition outcomes. We developed an optional, complementary module for the project-level women's empowerment in agriculture index (pro-WEAI) to measure health- and nutrition-related agency (pro-WEAI + HN). Our method for developing related indicators used data collected from six agricultural development programmes implemented across Bangladesh, Burkina Faso and Mali (pooled sample = 12,114) and applied psychometric analysis (exploratory and confirmatory factor analysis) and the Alkire−Foster methodology. Results revealed seven indicators covering women's agency in the areas of her own health and diet; her health and diet during pregnancy; her child's diet; breastfeeding and weaning; purchasing food and health products; and acquiring food and health products. Multigroup confirmatory factor analysis revealed measurement invariance across contexts and samples. Tests of association (Cramer's V) and redundancy suggest that the pro-WEAI + HN indicators measured aspects of agency that are distinct from the core pro-WEAI. The uptake of these indicators in studies of nutrition-sensitive agricultural development projects may strengthen the evidence on how such programming can enhance women's empowerment to improve health and nutrition outcomes for themselves and their children.